2014
DOI: 10.3109/10408363.2014.992064
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width: A simple parameter with multiple clinical applications

Abstract: The red blood cell distribution width (RDW) is a simple and inexpensive parameter, which reflects the degree of heterogeneity of erythrocyte volume (conventionally known as anisocytosis), and is traditionally used in laboratory hematology for differential diagnosis of anemias. Nonetheless, recent evidence attests that anisocytosis is commonplace in human disorders such as cardiovascular disease, venous thromboembolism, cancer, diabetes, community-acquired pneumonia, chronic obstructive pulmonary disease, liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
895
5
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 860 publications
(948 citation statements)
references
References 161 publications
25
895
5
23
Order By: Relevance
“…There are a number of studies indicating that RDW has been influenced by inflammation and oxidative stress, and a strong correlation between RDW and inflammatory markers, C-reactive protein, and sedimentation rate has been observed [11][12][13]. We found that inflammation-related CBC parameters were similar between the groups; however, this was not in agreement with our working hypothesis.…”
Section: Discussioncontrasting
confidence: 57%
“…There are a number of studies indicating that RDW has been influenced by inflammation and oxidative stress, and a strong correlation between RDW and inflammatory markers, C-reactive protein, and sedimentation rate has been observed [11][12][13]. We found that inflammation-related CBC parameters were similar between the groups; however, this was not in agreement with our working hypothesis.…”
Section: Discussioncontrasting
confidence: 57%
“…In the last years, a number of studies have demonstrated that this simple parameter, automatically reported by laboratory blood analyzers, may have multiple clinical applications: an increased RDW has a high negative predictive value (NPV) for diagnosing a variety of disorders and may be useful to evaluate short-and long-term prognosis in cardiovascular and thrombotic disorders (4)(5)(6). C o n s i d e r a b l e a t t e n t i o n h a s b e e n p a i d f o r t h e observation that RDW is a strong predictor of all-cause, cardiovascular-and cancer-related mortality in the general population ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Salvagno GL et al 18 describe red blood cell distribution width (RDW) as a simple and inexpensive parameter, which refl ects the degree of heterogeneity of erythrocyte volume (conventionally known as anisocytosis); which is traditionally used in laboratory hematology for differential diagnosis of anemias. Nonetheless, recent evidence attests that anisocytosis is commonplace in human disorders such as cardiovascular disease, venous thromboembolism, cancer, diabetes, community-acquired pneumonia, chronic obstructive pulmonary disease, liver and kidney failure, as well as in other acute or chronic conditions.…”
Section: Discussionmentioning
confidence: 99%